Las facultades de la Junta de Acreedores frente a los derechos de los accionistas de empresas en concurso: A propósito de una Sentencia del TC y las operaciones acordeón - Valdivieso López, Erika J. (Revista de Derecho, 2019)
The present job conducts an analysis of the faculties that a Board of Creditors from a company in bankruptcy and their limits in the light of the Constitutional Tribunal Sentence on File N° 00228-2009-PA/TC, in which the Empresa Agraria Chiquitoy S.A.’s shareholders demand is well-founded and orders for his rights, from which he had deprived when an accordion operation (reduction of capital to zero and increase of capital in a simultaneous way) as such to be returned, with capitalization of the company’s shareholders’ credits.